Scaling readiness: Learnings from applying a novel approach to support scaling of food system innovations - Schut, Marc; Leeuwis, Cees; Sartas, Murat; Taborda Andrade, Luis Alejandro; Etten, Jacob van; Müller, Anna; Tran, Thierry; Chapuis, Arnaud; Thiele, Graham (Springer, 2022)
Scaling of innovations is a key requirement for addressing societal challenges in sectors such as agriculture, but research for development programs struggles to make innovations go to scale. There is a gap between new complexity-aware scientific theories and perspectives on innovation and practical approaches that can improve strategic and operational decision-making in research for development interventions that aim to scale innovations. To bridge this gap, Scaling Readiness was developed. Scaling Readiness is an approach that encourages critical reflection on how ready innovations are for scaling in a particular context for achieving a particular goal and what appropriate actions could accelerate or enhance scaling to realize development outcomes. Scaling Readiness provides decision support for (1) characterizing the innovation and innovation system; (2) diagnosing the current readiness and use of innovations; (3) developing strategies to overcome bottlenecks for scaling; (4) facilitating multi-stakeholder negotiation and agreement; and (5) navigating the implementation process. This chapter explains how Scaling Readiness was used in the CGIAR Research Program on Roots, Tubers and Bananas (RTB) and describes how Scaling Readiness informed the design and management of the RTB Scaling Fund, an instrument for identifying and nurturing scaling-ready innovations. We introduce the key principles and concepts of Scaling Readiness and provide a case study of how Scaling Readiness was applied for scaling a cassava flash dryer innovation in different countries in Africa and Central America. The chapter concludes with a reflection and recommendations for the further improvement and use of Scaling Readiness.